Effects of long-term culture on the biological characteristics and RNA profiles of human bone-marrow-derived mesenchymal stem cells - Shan Wang; Ziming Wang; Hongjun Su; Fenglei Chen; Mengjun Ma; Wenhui Yu; Guiwen Ye; Shuizhong Cen; Rujia Mi; Xiaohua Wu; Wen Deng; Pei Feng; et al. (Elsevier, 2021)
Expansion in vitro prior to mesenchymal stem cells (MSCs) application is a necessary process. Functional and genomic stability has a crucial role in stem-cell-based therapies. However, the exact expression and co-expressed profiles of coding and non-coding RNAs in human bone marrow (BM)-MSCs in vitro aging are still lacking. In the present studies, the change of morphology, immunophenotype, and capacity of proliferation, differentiation, and immunoregulation of MSCs at passage (P) 4, P6, P8, P10, and P12 were investigated. RNA sequencing identified that 439 mRNAs, 65 long noncoding RNAs (lncRNAs), 59 microRNAs (miRNAs), and 229 circular RNAs (circRNAs) were differentially expressed (DE) in P12 compared with P4, with a similar trend in P6. Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and gene set enrichment analysis (GSEA) identified several significant biological processes and pathways, including binding, ossification, and Wnt and PPAR signaling pathways. Interaction and co-expression/localization analyses were performed for DE mRNAs and lncRNAs, and several key lncRNAs, circRNAs, and important pathways like autophagy and mitophagy were identified in the competing endogenous RNA (ceRNA) network. Some key RNAs found in the bioinformatics analysis were validated. Our studies indicate that replicative senescence of MSCs is a continuous process, including widespread alterations in biological characteristics and global gene expression patterns that need to be considered before therapeutic applications of MSCs.